(untitled) (Veterinary Science, 2025)
To ensure the safety of the salads served in the University Cafeteria menus, the microbiological quality of the raw materials was studied. Two hundred samples (80 lettuce, 40 tomato, 40 cabbage, and 40 carrot) were analyzed following the official methodology (Mesophilic Aerobic Count, MPN/g of Escherichia coli, detection of Salmonella spp., Listeria monocytogenes, E. coli STEC O157, E. coli STEC non-O157, and Shigella spp.). Three strains of Listeria monocytogenes were isolated (one from cabbage and two from lettuce), two of L. seeligeri, five of L. welshimeri, and one strain of L. ivanovii. One strain of Salmonella and one strain of Shigella flexneri, both from lettuce. Two strains of E. coli O157 strains were isolated from cabbage, one stx-1 positive, and the other stx-2 positive. Three non-O157 STEC were isolated: a stx-2 positive O45 strain from carrots, and stx-1 and stx-2 positive O145 strain from carrots, and an stx-2 positive serotype O45 strain from lettuce. Mesophilic counts ranged from 105 to 108 CFU/g for cabbage and carrots, 102 to 107 CFU/g for tomatoes, and from 103 to 107 CFU/g for lettuce. E. coli counts exceeded the permissible limits in 14 samples. These data highlight the need for control upon receipt of raw materials, planning a sanitation strategy, and subsequent safety control